Algae flora of graduation towers in the town of Ciechocinek - Luścińska, Marta; Gadziemska, Malwina (Ecological Questions, 2011)
The research was focused on algae occurring on wooden constructions of three graduation towers, which are the main elements of historical salt production technology, located in the health-resort of Ciechocinek in the region of Kujawy. The research also included algae occurring in reservoirs with brine condensed on graduation towers, as well as algae from puddles and the soil under the graduation towers. 52 algae taxa were recorded in the collected material. Representatives of the following phyla were distinguished: 5 taxa of Cyanoprokaryota, 46 taxa of Heterokontophyta (including 44 taxa of diatoms) and 7 taxa of Chlorophyta. Samples from the sites with brine of the lowest salt concentration (4%) turned out to be the most abundant in species.